Long term outcomes of patients with skull-base low-grade chondrosarcoma and chordoma patients treated with pencil beam scanning proton therapy. Issue 1 (July 2016) - Weber, Damien C.; Malyapa, Robert; Albertini, Francesca; Bolsi, Alessandra; Kliebsch, Ulrike; Walser, Marc; Pica, Alessia; Combescure, Christophe; Lomax, Antony J.; Schneider, Ralf
Abstract: Purpose: To evaluate the long term tumor control and toxicity of skull base tumors treated with pencil beam scanning proton therapy (PT). Materials and methods: PT was delivered to 151 (68%) and 71 (32%) chordoma and chondrosarcoma (ChSa) patients, respectively. Mean age of patients was 40.8 ± 18.4 years and the male to female ratio was 0.53. The postoperative tumor was abutting the brainstem or optic apparatus in 71 (32.0%) patients. The postoperative mean gross tumor volume (GTV) was 35.7 ± 29.1 cm 3 . The delivered mean PT dose was 72.5 ± 2.2 GyRBE. Results: After a mean follow-up of 50 (range, 4–176) months, 35 local (15.8%) failures were observed between 10.9 and 85.4 months. The estimated 7-year LC rate for chordoma (70.9%; CI95% 61.5–81.8) was significantly lower compared to the LC rate for ChSa patients (93.6%; 95%CI 87.8–99.9; P = 0.014). The estimated 7-year distant metastasis-free- and overall survival rate was 91.6% (95%CI 91.6–98.6) and 81.7% (95%CI 74.7–89.5), respectively. On multivariate analysis, optic apparatus and/or brainstem compression, histology and GTV were independent prognostic factors for LC and OS. The 7-year high grade toxicity-free survival was 87.2 (95%CI 82.4–92.3). Conclusions: PBS PT is an effective treatment for skull base tumors with acceptable late toxicity. Optic apparatus and/or brainstem compression, histology and GTV allow independent prediction of the risk of local failure and death in skull base tumor patients.